Three new species of the genus Leucopholis Dejean, 1833 (Coleoptera, Scarabaeidae, Melolonthinae, Leucopholini) from the Philippines and designation of a neotype for L. semperi Brenske, 1896 - Orlando A. Calcetas (European Journal of Taxonomy, 2023)
Three species of Leucopholis Dejean, 1833 chafers from the Philippines are described and illustrated: Leucopholis stainesi sp. nov., L. bezdeki sp. nov. and L. ratcliffei sp. nov. A neotype is designated for Leucopholis semperi Brenske, 1896. A revised key to the species of Leucopholis in the Philippines is provided.